Cellular hierarchy for understanding heterogeneity of acute myeloid leukaemia with t(8;21)/RUNX1‐RUNX1T1 - Yibo Wu; Xiaolin Yuan; Xiaoyu Lai; Lizhen Liu; Yue Liang; Lihong Ni; Luxin Yang; Shanshan Hu; Jimin Shi; Jian Yu; Yanmin Zhao; Weiyan Zheng; et al. (Clinical & Translational Immunology, 2025)
Abstract Objectives Differentiation hierarchies in myeloid malignancies influence therapeutic response and prognosis. Acute myeloid leukaemia (AML) with t(8;21) is one of the most recurrent genetic subtypes of AML and is considered a distinct entity with shared characteristics. However, clinical outcomes remain markedly heterogeneous. This study aimed to investigate the relationship between leukaemic arrest at specific differentiation stages, genomic profiles and clinical outcomes in t(8;21) AML. Methods We conducted a retrospective study involving 338 patients with t(8;21) AML from three clinical centres in China. Patients received either chemotherapy alone (49.11%, n = 166) or chemotherapy followed by allogeneic haematopoietic stem cell transplantation (allo‐HSCT; 41.72%, n = 141). Immunophenotypic profiling classified patients into progenitor subgroups: MPP (20.12%, n = 68), lymphoid‐primed multi‐potent progenitor (14.50%, n = 49), CMP (12.72%, n = 43), GMP (24.85%, n = 84) and GP/MP (10.36%, n = 35). Based on differentiation stage, patients were categorised as primitive (Immuno‐Prim; 47.34%, n = 160) or monocytic (Immuno‐Mono; 35.21%, n = 119). Results The Immuno‐Mono group was associated with lower 2‐year overall survival (OS) and a higher 2‐year cumulative incidence of relapse (CIR) compared to the Immuno‐Prim group. Patients with a KIT mutation had poorer 2‐year OS and higher 2‐year CIR than those without the mutation. In the allo‐HSCT cohort, the Immuno‐Mono group continued to show lower 2‐year OS and higher 2‐year CIR relative to the Immuno‐Prim group. Neither gene mutations (aside from KIT) nor chromosomal losses significantly affected OS or CIR. Conclusions Leukaemic differentiation stage independently predicts post‐treatment outcomes in t(8;21) AML. Arrest at specific myeloid stages correlates significantly with genetic aberrations, clinical presentation, therapeutic response and survival.